Experiences from Implementation of Lean Production: Standardization versus Self-management: A Swedish Case Study - Oudhuis, Margareta; Tengblad, Stefan (Nordic Journal of Working Life Studies, 2013)
In this article, we discuss important aspects of the perceived problematic relationship between self-management and standardization. The article presents data from three case studies conducted within manufacturing companies in Sweden, where the popularity of lean production has led to a renaissance for short-cycle and standardized assembly work in settings that traditionally have made use of sociotechnical production design. The data suggest that the implementation has not contributed to an increased commitment, smooth operations, and capacity for change and innovation. Despite these not so positive results, it is argued that it is possible to combine self-management principles with lean production and standardization if 1) the implementation of lean is done with a contextual sensitivity, 2) a balance is reached between the use of standards on the one hand and work enrichment on the other, and 3) a feeling of ownership as regards both implementation and production process is upheld among the product on personnel.